Defying Europe? The Euroscepticism of radical right and radical left voters in Western Europe. Issue 8 (17th November 2021) - Carrieri, Luca; Vittori, Davide
ABSTRACT: Radical Left Parties (RLPs) and Radical Right Parties (RRPs) parties have adopted similar platforms over EU economic integration, rejecting further budgetary/economic authority transfers towards the EU. During the Euro crisis, EU-led management of the recession, constraining budgetary independency, may have worsened public concerns over the loss of state sovereignty on economic prerogatives. Although RLPs and RRPs have conveyed to voters anti-EU budgetary messages, we do not know if the electors have responded to this cueing activity. Thus, this paper seeks to understand whether, during the Euro crisis, voters supported the RLPs and RRPs due to anti-EU budgetary positions or not in Western Europe. On the one hand, we show that voters have electorally rewarded RRPs on the anti-EU budgetary issues, profiling themselves as Euro-rejectionists . On the other hand, we found that voters have not significantly matched RLP anti-EU budgetary stances, perhaps expressing favourable orientations towards the EU inter-state solidarity.